PRIVACY COMMODIFICATION VIA YOUTUBE SOCIAL MEDIA: Study on dr. Richard Lee's YouTube Channel, MARS - Mutiah; Miftakhoiria Novalia; Leti Karmila (Metafora: Education, Social Sciences and Humanities Journal, 2025)
Various questions related to privacy intersect with norms of politeness. Privacy contains the value of controlling reputation and there is protection for it in the state constitution. This research is aimed at finding out or understanding privacy that is commodified on the YouTube channel dr. Richard Lee, MARS, the process of commodification of privacy based on the political economy perspective of Vincent Mosco's communication, and the reasons why privacy is commodified and its commonplace appearance in public spaces. This research is qualitative research with content analysis methods. In this research there are five pieces of content from the YouTube channel dr. Richard Lee, MARS which was analyzed through observation techniques and documentation. The research results show that there is a commodification of privacy regarding a person's personality, and a person's communication related to sexual orientation, personality, past, and disclosure of the contents of a person's conversations through long video formats or short videos by digging up in-depth information about the source or also digging up information about other people related to the source. Commodification on YouTube is related to the monetization of content, such as through advertising or selling certain products. On the YouTube channel dr. Richard Lee, MARS there is a shift in content content. The commodification of privacy and its commonplace appearance are related to the term hyperreality, and the public's misconceptions about the privacy of public figures. Keywords: Commodification, Privacy, Social Media, YouTube